The Effect of Irrigation with Treated Municipal Wastewater and Agricultural Drainage Water on Soil Chemical Properties. Issue 6 (26th March 2023) - Dadfar, Hassan; Albaji, Mohammad; Boroomand Nasab, Saeed
ABSTRACT: This study was carried out to investigate the effect of irrigation with treated municipal wastewater and agricultural drainage water on Ahvaz (southwest Iran) soil chemical properties in 24 plots with 1 × 1 (m) area in farm No. 1 of Shahid Chamran University of Ahvaz in 2018–2019. The experiment was carried out as a factorial experiment in a completely randomized block design with three replications. The experiment factors included eight irrigation treatments (A: Irrigation with Karun River water as control), (F: Irrigation with treated municipal wastewater). (Z: Irrigation with agricultural drainage water), (Z1F1: 30% Agricultural drainage water +70% Treated municipal wastewater), (Z2F2: 70% Agricultural drainage water +30% Treated municipal wastewater), (Z3F3: 50% Agricultural drainage water +50% Treated municipal wastewater), (Z4A4:50% Agricultural drainage water +50% Karun River water), (F5A5: 50% Treated municipal wastewater +50% Karun River water), at five time levels (including pre-treatment, first month, second month, fourth month, sixth month were performed at three depths (0–20), (20–40), (40–60) cm. The traits examined in this experiment were pH (Acidity), EC (Electrical Conductivity), Ca 2+ (Calcium), Mg 2+ (Magnesium), Na+(Sodium), K+(Potassium), HCO3 -(Bicarbonate), CO3 −2 (Carbonate), SAR (Sodium Adsorption Ratio). Experimental factors had different effect on studied traits. Results showed that with increasing soil depth, all treatments except carbonate and acidity decreased. Calcium, magnesium, sodium and bicarbonate showed significant differences over time (P < 0.01). Non-significant difference in potassium was observed during this time (P > 0.01). There was significant increase in salinity over time (P < 0.01). In T1 period Karun River water showed the highest salinity amount irrigation treatment. Also, F5A5 treatment had the lowest concentration of Ca 2+, Mg 2+, K+ and the highest concentration of SAR. The Z4F4 treatment showed the lowest concentration of SAR and the highest concentration of Mg 2+ .The Z treatment had the lowest concentration for Mg 2+ . The A treatment showed the lowest concentration for HCO3 -. The F treatment had the highest concentration for Ca 2+ ; the Z3F3 treatment had the highest concentration for K+, the Z1F1 and Z2F2 treatments showed the highest concentration in terms of SAR.